Metaphor of the ancients: A study in the critical Arab heritage until the end of the fourth century AH - Al-Qarni, Aqaila Muhammad (Journal of Arabic Language Sciences and Literature, 2022)
This study was concerned with highlighting the value of metaphor and its place in the critical Arab heritage until the end of the fourth century AH. It also sought to clarify the controls that ensure their validity and quality, and the general critical position on them if the poet exceeds the custom in his use of them.